AN ANALYSIS OF SYNTACTICAL DEVIATION IN ED SHEERAN'S SELECTED SONG LYRICS - Gafur, Abdul; Arifin, M. Bahri; Rahayu, Famala Eka Sanhadi (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2021)
The objectives of this research are to find out the types and the functions of syntactical deviation used in Ed Sheeran’s selected song lyrics. This analysis includes to qualitative method. This research used seven famous songs of Ed Sheeran as the source of data. The data were taken from the lines of the seven selected songs of Ed Sheeran that considered to have syntactical deviation. Through the findings of the analysis, there were 7 (seven) types of syntactical deviation namely double negation, omission, deviation of verb, deviation of preposition, deviation of article, anastrophe, and hypallage were employed in the selected songs of Ed Sheeran. The omission type was the most frequently used in the song lyrics of Ed Sheeran. Functionally, it is to indicate an omission of unnecessary words or information. It means that the lyrics of the song mostly omitted by Ed Sheeran, it is to make the song denser which means it talks a lot in a brief statement and also match with the melody or music. Otherwise, overgeneralization, deviation of noun, deviation of pronoun, and hysteron proteron were not found in the selected songs of Ed Sheeran, because those types of syntactical deviation cannot represent the motives that Ed Sheeran want to convey in his song lyrics.